Sweet potato NAC transcription factor NAC43 negatively regulates plant growth by causing leaf curling and reducing photosynthetic efficiency - Sun, Sifan; Li, Xu; Nie, Nan; Chen, Yanqi; Gao, Shaopei; Zhang, Huan; He, Shaozhen; Liu, Qingchang; Zhai, Hong (Frontiers in Plant Science, 2023)
Leaf is one of the important organs for plant growth and development. Although there have been some reports on leaf development and the establishment of leaf polarity. However, their regulatory mechanism is not very clear. Here, we isolated a NAC transcription factor (TF) gene IbNAC43 from Ipomoea trifida, which is a wild ancestor of sweetpotato. It was highly expressed in leaves and encoded a nuclear localization protein. Overexpression of IbNAC43 caused leaf curling and inhibited the growth and development of transgenic sweetpotato plants. The chlorophyll content and photosynthetic rate in transgenic sweetpotato were significantly lower than those in wild type (WT) plants. Scanning electron microscopy (SEM) and paraffin section showed that the ratio of cells number in the upper and lower epidermal of the transgenic plants leaves was unbalanced, and the abaxial epidermal cells were unregular and uneven in transgenic plants. In addition, the xylem of transgenic plants was more developed than that of WT plants, and lignin content was significantly higher than that of WT. qRT-PCR analysis showed that overexpression of IbNAC43 upregulated the genes involved in leaf polarity development and lignin biosynthesis in transgenic plants. Moreover, we found that IbNAC43 could directly activate the expression of leaf adaxial polarity related genes IbREV and IbAS1 by binding to their promoters. These results showed that IbNAC43 might act a critical role in plant growth by affecting establishment of leaf adaxial polarity, and this study provided a new insight for leaf development.